Estimation of regional scale effective infiltration using an open source hydrogeological balance model and free/open data. (June 2018) - Rossi, Mauro; Donnini, Marco
Abstract: Effective infiltration (EI) is the amount of precipitation infiltrating into the soil and recharging the aquifers. EI is estimated using direct or indirect methods or using water balance models. Direct and indirect methods lead to biased EI estimates, since based on simplified schemas of groundwater bodies and of their recharge mechanisms. Water balance models include different processes and variables, but they are seldom applied due to the limited availability of the input data, particularly at regional scales. We propose a method for EI estimation over large areas based on a monthly water balance model exploiting open source software and free/open data. The model integrates procedures to estimate EI and other water balance components, accounting for the uncertainty of input data. The model is calibrated in the Central Apennines (Italy), where EI reference values are available from the literature, and later applied in the Alps, where regional EI estimates are missing. Highlights: Presented a method to estimate Effective Infiltration in large areas, improving Thornthwaite-Mather model and using open data. Minimum, maximum and mean values of model components estimated from the spatial variability of input data. Model calibrated in Central Apennines, where effective infiltration benchmark data are known from the scientific literature. The calibrated model was applied in the Alps allowing regional estimations of Effective Infiltration. The method is applicable for most of Europe and part of Eurasia where similar open input data are available.